Restrictions And Responsibilities of Visitors to Surabaya Zoo - Bahira, Arimbi Salma; Larasati, Diyas Age; Kurniasih, Anisah; Nabilah, Qonita Ayu; Noerdianasari, Miranda; Prayogi, Panji Agung (International Journal of Universal Education, 2024)
Aim: The aim of this research is to identify and analyze the limitations and responsibilities of visitors to the Surabaya Zoo (KBS) in maintaining animal welfare, environmental cleanliness and preserving conservation functions. Method: This research method uses a direct observation approach and literature study to obtain empirical data and theoretical perspectives. Result and Discussions: The research results show that most violations of boundaries by visitors are caused by a lack of understanding and awareness of the applicable rules, such as throwing rubbish out of place, urinating carelessly, smoking carelessly and spitting carelessly. Conclusion: To increase visitor compliance, more intensive education is needed through information boards, awareness campaigns and stricter supervision. It is hoped that this study can become the basis for developing visitor management policies that support KBS conservation goals in a sustainable manner.